2021
DOI: 10.3233/jpd-202259
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic Stimulation for Camptocormia in Parkinson’s Disease: Association of Volume of Tissue Activated and Structural Connectivity with Clinical Effectiveness

Abstract: Background: Deep brain stimulation of the subthalamic nucleus (STN-DBS) has been reported to be effective for camptocormia in Parkinson’s disease (PD). However, the association between clinical effectiveness and the stimulated volumes or structural connectivity remains unexplored. Objective: To investigate the effectiveness of STN-DBS for treating camptocormia in PD and its association with volumes of tissue activated (VTA) and structural connectivity. Methods: We reviewed video recordings of patients who had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…Furthermore, in a small study of three patients with PD, two with bilateral DBS in the STN and one with bilateral GPi DBS, no or mild improvement of trunk flexion was seen in the two patients with DBS in the STN but a moderate improvement was seen in the patient with GPi DBS [ 41 ]. The results of the current study for DBS in the STN showed results that are more favorable (consistent with others, e.g., [ 4 ]) and could be a reflection of a longer interval between testing and DBS surgery. It should also be noted that in a systematic review by Chieng and colleagues [ 6 ], 68% of patients with PD saw an improvement to the degree of trunk flexion with DBS with an average reduction of 78.2% in flexion angle.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Furthermore, in a small study of three patients with PD, two with bilateral DBS in the STN and one with bilateral GPi DBS, no or mild improvement of trunk flexion was seen in the two patients with DBS in the STN but a moderate improvement was seen in the patient with GPi DBS [ 41 ]. The results of the current study for DBS in the STN showed results that are more favorable (consistent with others, e.g., [ 4 ]) and could be a reflection of a longer interval between testing and DBS surgery. It should also be noted that in a systematic review by Chieng and colleagues [ 6 ], 68% of patients with PD saw an improvement to the degree of trunk flexion with DBS with an average reduction of 78.2% in flexion angle.…”
Section: Discussionsupporting
confidence: 91%
“…The GLM ANOVA of the main factor, vision, revealed that the movement amplitudes were larger with eyes closed than with eyes open at all recorded sites (p�0.020) (Table 5 and Fig 4). The main factor, adaptation, revealed that the PD group made marked reductions of the body movement over time at all recorded sites (p<0.001).…”
Section: Effects Of Dbs Vision and Adaptationmentioning
confidence: 89%
See 3 more Smart Citations